Hemoglobin St. Louis [beta 28 (B10) Leu replaced by Gln]: crystal structure of the fully reduced (deoxy) form. - Anderson, N L (1976)
The three-dimensional structure of fully reduced Hb St. Louis has been determined to 3.5 A resolution. The difference electron density map clearly shows the site of the mutation and the effects it produces. Glutamine B10 and histidine E7 (the distal histidine) swing towards each other and, between them, stabilize a water molecule in the normally hydrophobic heme pocket. This creation of an aqueous microenvironment near the heme accounts for the thermal instability, high rate of methemoglobin formation, and increased oxygen affinity observed in solution studies of the mutant as described in the preceeding paper. Other than a small increase in tilt of the heme, virtually no further stereochemical disturbances result.